Prediction Value of Visceral Obesity Related Indices for Visceral Obesity in Chinese Patients with Type 2 Diabetes Mellitus - Tan Y; Li K; Ma J; Luo Z; Gong S; Mao J; Zhou Q; Zhou H; Gan S (Diabetes, Metabolic Syndrome and Obesity, 2025)
Yajuan Tan,1 Kang Li,1 Jinhua Ma,2 Zhao Luo,2 Shijun Gong,3 Jing Mao,4 Quan Zhou,4 Haifeng Zhou,5 Shenglian Gan5 1Department of Medicine, Jishou University, Jishou, People’s Republic of China; 2Nanhua University, Hengyang, People’s Republic of China; 3Department of Ultrasonography, The First People’s Hospital of Changde City, Changde, People’s Republic of China; 4Department of Science and Education, The First People’s Hospital of Changde City, Changde, People’s Republic of China; 5Department of Endocrinology, The First People’s Hospital of Changde City, Changde, People’s Republic of ChinaCorrespondence: Shenglian Gan, Department of Endocrinology, The First People’s Hospital of Changde City, Changde, 415003, People’s Republic of China, Tel +8618173661153, Email gslghy03@sina.comPurpose: Visceral obesity (VO) has a significant impact on the progression of type 2 diabetes mellitus (T2DM) and insulin resistance. This study aims to evaluate the correlation and predictive utility of visceral obesity-related indices in T2DM patients with VO.Patients and Methods: This study included 2438 Chinese patients with T2DM. Visceral fat area (VFA) was assessed using bioelectrical impedance analysis (BIA), with VFA ≥ 80 cm² defined as VO. Multifactor logistic regression analysis was used to explore the relationship between VO and various indices in T2DM patients, including the Chinese visceral adiposity index (CVAI), metabolic score for visceral fat (METS-VF), new visceral adiposity index (NVAI), visceral adiposity index (VAI), waist circumference (WC), body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR). Receiver operating characteristic (ROC) curves were plotted, and the area under the curve (AUC) was used to evaluate the ability of these indices to screen for VO in T2DM subjects. Pearson correlation analysis was performed to analyze the correlation between these indices and VFA.Results: 1226 (50.29%) T2DM patients were found to have VO. The prevalence of VO was higher in males than in females. Among the total population, WC had the best predictive performance for VO (AUC=0.8833, optimal cutoff =90.05). CVAI was the best predictor for males (AUC=0.8837, optimal cutoff =117.39), while WC performed best in females (AUC=0.8733, optimal cutoff=87.25). Among individuals with normal WC, CVAI for males and METS-VF for females had the best predictive performance for VO.Conclusion: There exists a strong correlation between VO and its related indicators in patients with T2DM. WC, CVAI, and METS-VF are optimal predictive indices for VO in this patient population.Keywords: visceral obesity, visceral obesity related indices, type 2 diabetes mellitus